MANAJEMEN KRISIS DAN REPUTASI PERUSAHAAN TAKSI KONVENSIONAL TERKAIT DEMONSTRASI PENOLAKAN TAKSI ONLINE Studi Kasus pada Blue Bird Group - Febriyani, Arifa Rachma (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2017)
The demonstration to refuse online taxi Uber and Grab driven by PPAD Jadetabek on March 22 is a crisis for Blue Bird Group that has been known to have a positive reputation. This is due to the demonstrations was allegedly provoked by one of the Blue Bird driver's. The purpose of this study is to describe the Blue Bird Group's PR strategy in managing the crisis as a result of the demonstration in order to save the reputation of their organization. The results showed PR Blue Bird Group implements several crisis response strategies, such as execuse, apologize, compensation, and reminders.Â